An Interesting Case of Osteolysis With Accompanying Metallosis in a Primary Total Knee Arthroplasty - Collin Lamba, MD (Elsevier, 2021)
Arthroplasty implants are comprised of metal alloys designed to function within the human body. Implant-related issues and associated soft-tissue reactions have been well documented for modular revision hip and knee constructs. This case highlights findings of metallosis in the context of polyethylene wear in a failed primary total knee arthroplasty. Fretting of a polyethylene reinforcement pin within the tibial baseplate as a direct result of knee joint instability appears to be the root cause of observed periprosthetic metallosis. Enhanced design principles and improved polyethylene locking mechanisms may be useful to potentially mitigate fretting-related issues in future knee replacement designs. The authors recommend surveillance in patients with this construct especially when prosthetic instability is present.